(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of the Massed Practice learning method on improving sepak takraw skills in university students. This study used an experimental method with a one-group pretest-posttest design. This study involved 20 students of the Physical Education, Health, and Recreation (PJKR), Makassar State University who took the Sepaktakraw game course. Sepak takraw skills were measured twice, namely before (pretest) and after (posttest) the application of the Massed Practice learning method. The instrument used in this study was a sepak takraw skills test that included accuracy and ball control. Data were analyzed using a t-test to determine differences in results before and after treatment. The results showed a significant increase in sepak takraw skills after the application of the Massed Practice method (0.000 <0.05). Thus, this method is effective for use in the process of learning basic sepaktakraw techniques, especially to improve students’ sepak takraw skills.